Project-based Collaborative Learning on Student Concept-Application with Different Prior Knowledge - Sukmawati, Fatma (Universitas Negeri Malang, 2023)
This research was determined the effect of Project-based Collaborative Learning (PBCL), Project-based Learning (PjBL), and conventional learning on students' concept application skills in learning biology, considering the prior knowledge, as well as the interaction between learning strategies and students' prior knowledge. This research was designed as a quasi-experiment using pre-post-test non-equivalent control group One hundred high school students participated as research samples. Observations, tests and documentation were conducted as data collection techniques. Data on students' concept application skills were technically obtained from tests. The data were analyzed using ANCOVA. The statistical test results showed that the learning strategies (PBCL, PjBL, and conventional) significantly affected students' ability to apply biological concepts. The students' prior knowledge results also showed a significant influence on students' ability to apply concepts. The interaction between learning strategies and students' prior knowledge also influences their ability to apply concepts. These findings indicate that PBCL significantly contributes to the concepts understanding in learners' daily lives. However, it is recommended that future research addresses other topics in both elementary and junior high schools. Further research can also focus on measuring higher learning outcomes from concept application, such as concept analysis, synthesis, evaluation, problem solving, and other students' skill abilities.AbstrakTujuan penelitian ini adalah untuk mengetahui pengaruh Project-based Collaborative Learning (PBCL), Project-based Learning (PjBL), dan pembelajaran konvensional terhadap kemampuan penerapan konsep peserta didik dalam pembelajaran biologi, dengan mempertimbangkan konsep pengetahuan awal, serta interaksi antara strategi pembelajaran dan pengetahuan awal yang dimiliki peserta didik. Penelitian ini dirancang dengan jenis quasi eksperimen menggunakan pre-post-test non-equivalent control group. Seratus peserta didik tingkat SMA berpartisipasi sebagai sampel penelitian. Observasi, tes, dan dokumentasi dilakukan sebagai teknik pengumpulan data. Data kemampuan penerapan konsep peserta didik secara teknis diperoleh dari tes. Selanjutnya, data dianalisis menggunakan ANCOVA. Hasil uji statistik menunjukkan strategi pembelajaran (PBCL, PjBL, dan konvensional) berpengaruh signifikan terhadap kemampuan peserta didik dalam menerapkan konsep biologi. Hasil pengetahuan awal peserta didik juga menunjukkan pengaruh signifikan terhadap kemampuan penerapan konsep peserta didik. Interaksi antara strategi pembelajaran dan pengetahuan awal peserta didik juga berpengaruh terhadap kemampuan penerapan konsepnya. Temuan ini menunjukkan bahwa PBCL secara signifikan berkontribusi pada pemahaman konsep dalam kehidupan peserta didik sehari-hari. Namun, disarankan agar penelitian selanjutnya membahas tentang topik lain baik di SD maupun SMP. Penelitian selanjutnya juga dapat berfokus pada pengukuran hasil belajar yang lebih tinggi dari aplikasi konsep, seperti analisis konsep, sintesa, evaluasi, problem solving, dan kemampuan keterampilan peserta didik lainnya.